Phytophthora nicotianae causing root and stem rot on Dieffenbachia picta in Argentina - Palmucci, Hemilse Elena (2011)
Dieffenbachia picta is a worldwide appreciated crop due to its ornamental value. In Argentina it is cultivated in warm provinces and in the outskirts of Buenos Aires city, where in spring 2007 a great amount of plants were lost in commercial greenhouses. Symptoms such as wilting and soaked lesions in the basal leaves began in four- to six-month-old plants causing plants to wilt due to basal stem and root rot processes. A Peronosporomycete was consistently isolated from diseased tissues. The pathogen was identified as Phytophthora nicotianae based on cultural characteristics, morphology of vegetative and reproductive structures, and on the analysis of the sequence of the nuclear ribosomal internal transcribed spacer (ITS) region. Pathogenicity tests were carried out and Koch's postulates were fulfilled. In complementary studies, the dieffenbachia varieties Alex, Compact, Camilla and Marianne were susceptible to the infection caused by P. nicotianae, whereas Tropic snow (D. amonea) was resistant. This is the first report of P. nicotianae causing stem and root rot of D. picta in Argentina and in the Americas.